CO2 Capture in Large Industries: The Post-Combustion Method - Lódolo, Maximiliano; Rausch, Martin (My University, 2023)
Abstract— This paper presents methods for CO2 capture that are important to address the problem of contamination in large scale industries. The impact of carbon dioxide in the environment is described to understand why it is important to capture it. Moreover, post-combustion capture methods are described as possible solutions. As well as this, the advantages and disadvantages of each method and a viability analysis are introduced. It is expected that this paper may mark a way to achieve a reduction in contamination in large scale industries.

Resumen— Este trabajo presenta los métodos de captura de CO2 que son importantes para resolver el problema de la contaminación en grandes industrias. El impacto del dióxido de carbono en el ambiente es descrito para entender por qué es importante capturarlo. Además, se describen los métodos de captura de post combustión como posible solución, y también se presentan las ventajas y desventajas de cada método y se hace un análisis de viabilidad. Se espera que este trabajo marque un camino para lograr una reducción de contaminación en industrias a gran escala.
Keywords: Inglés II; greenhouse gases; CO2 capture; post combustion method; gases de efecto invernadero; captura de CO2; metodo de postcombustión